Projeto, implementação e análise de uma fonte chaveada em alta frequência utilizando conversor flyback - Cruz, Víctor Peres Candido da (2022)
The object of this article is power electronics, which is an area of Electronics whose studies and applies the manipulation of the forms of conversions as well as the control of electrical energy through semiconductor devices. Among the main converters are: controlled and non-controlled rectifiers (Alternating Current (AC)-Direct Current (DC)), choppers (DC-DC), inverters (DC-AC), cyclic (AC-AC) and static switches (AC or DC). In general, applications require a continuous power supply for their respective operations, while the usual form of electrical energy is in alternating voltage, the circuits require a converter to direct voltage. Some applications have a converter attached to their Circuit, however others do not, which makes an external power supply necessary for its operation. There are several forms of configuration of power supplies that, in turn, can constitute linear or switched characteristics. This dissertation addresses a project that includes the implementation and analysis of a switched power supply in high frequency. The device developed consists of a rectifier, a DC-DC converter which used the flyback topology, a control mesh and an auxiliary source. All steps for its implementation are demonstrated, including the examination of the results obtained, which are compared and discussed at the end of the work, the results obtained in operation for open loop and closed loop proved to be satisfactory, thus reaching the objectives of the work.